Ph̄æn chumchon ʻOngkān B̨ōrihān Sūan Tambon Hūa S̄ưa (Samnak Palat, ʻOngkān B̨ōrihān Sūan Tambon Hūa S̄ưa, ʻAmph̄œ M̄æ Ta, Čhangwat Lampāng, 2006)
Plan for the local administration of Mae Ta District in Lampang Province, Northern Thailand.